The application of Narrative transportation in hard luxury business marketing (online marketing) on the potential customer in the Czech Republic. - Kapusta, Richard; Escobar Rios, Andrea; Martínez Pantoja, Yadira Ixchel; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2023)
The luxury industry plays a distinct part of the market and has experienced significant growth and transformation in recent years. The emergence of hard luxury as a separate market segment plays a crucial role in the luxury market. Hard luxury is characterized by high-quality, long-lasting products such as jewelry, watches, and precious accessories. These qualities capture the attention of consumers and marketers have to leverage this interest in order to obtain the best possible results and the desired goal in the market. In this context, understanding the motivation of current and potential customers plays a crucial role. The drivers leading the customers to make a purchase may vary. In terms of justification of the regular purchase of common goods customers tend to rationally justify trier purchase however with luxury goods, especially among hard luxury the motivation seems to be more emotionally based. Therefore the emotional drivers that influence consumer behavior and purchase decisions for hard luxury products are of paramount importance. This bachelor´s thesis dives into these drivers and explains their importance. The main focus is on the Czech and Slovak current and potential hard luxury customers and this thesis has an objective of the correct assigning of these drivers in order to leverage them for the theoretical and practical implications. Once these emotinal drivers are correctly assigned their potential integration will be examined mainly in the brand storytelling to effectively emerge the customer, creating the emotional interest in owning such goods and leveraging these drivers into the hard luxury brands marketing wit the focus on rising online marketing especially trough social media channels. To achieve this main goal, the thesis is divided into several subgoals. First, the thesis comprehensively explains the concept of luxury, luxury industry and the concept of the hard luxury itself.
Next, it explores the emotional drivers in hard luxury, focusing on specific emotional variables that play a significant role among Czech and Slovak custommers as well as providing a comprehensive ranking from the most important emotional drivers to the ones of the less significance. The emotional drivers has been dividend into individual and social dimension in order to provide comprehensive understanding of the emotional drivers emergeing from the individual perspective as well as provide understanding of the influence of the society and peoples surroundings on their preferences, brand loyalty, and purchasing decisions. With the understanding of these emotional drivers the recommendations for leveraging them in social media marketing are also provided, which includes the use of narrative transportation, emotional engagement, and other storytelling techniques to create compelling content with a focus on social media marketing that resonates with hard luxury consumers. This thesis aims to contribute to a deeper understanding of the emotional drivers in hard luxury and provide valuable insights for marketers and brand managers in the luxury industry. By identifying and analyzing these emotional drivers, the research hopes to help develop more targeted and effective marketing strategies for hard luxury brands, ultimately driving growth and success among Czech and Slovak customers in this competitive market segment. In order to guarantee the relevancy of the research and support its goals, a quantitative approach was employed. In order to obtain the desired goal the form of structured questionnaire has been chosen and distributed to a sample of current and potential hard luxury customers in the Czech Republic. The questionnaire is composed of questions related to demographics, peoples interest in hard luxury products, as well as a series of statements or questions that measure the importance of different emotional drivers influencing the importance of hard lu
Vedoucí práce: Andrea Escobar Rios
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor bakal. práce]; bakalářské práce; bachelor's theses